Health surveillance for SARS-CoV-2: infection spread and vaccination coverage in the schools of Modena province, Italy - Paduano, Stefania; Facchini, Maria Chiara; Borsari, Lucia; D’Alterio, Alessandra; Iacuzio, Laura; Greco, Antonella; Fioretti, Elisabetta; Creola, Giacomo; Kahfian, Zaynalabedin; Zona, Stefano; Bargellini, Annalisa; Filippini, Tommaso (Frontiers in Public Health, 2023)
Introduction. In Italy, over 4.8 million individuals aged 0-19 years have been infected with SARS-CoV-2. This study aims to evaluate the spread of SARS-CoV-2 within schools in Modena province and the influence of anti-SARS-CoV-2 vaccination coverage. Methods. We performed a survey in the period 1 September-15 December 2021, involving student population aged 0-19 years and related teachers screened for SARS-CoV-2 infection using nasopharyngeal swab after the detection of an index case within their class. During the study period, vaccination against SARS-CoV-2 was actively offered to all subjects aged ≥12 years. Results. A total of 13934 subjects were tested, 12534 students and 1400 teachers (594 classes). We identified a total of 594 and 779 index and secondary cases, respectively. We found that 9.8% of students and 10.6% of teachers were positive for SARS-CoV-2. Overall at the test time, 32.5% were vaccinated with at least one dose of anti-SARS-CoV-2 vaccine. Among secondary cases, 7.8% were vaccinated compared to 34.9% among negative tested subjects. A higher secondary attack rate was for non-vaccinated subjects rather than vaccinated ones (8.1% vs. 1.4%). Higher secondary attack rates were reported for subjects attending infant and primary school (5.9% and 9.6%, respectively). Lower secondary attack rates were for those who attended middle school (4.9%) and especially high school (1.7%). Conclusions. Our results highlight the differential spread of the infection within various educational settings and that the vaccination, available in the study period for the population aged ≥12, have mitigated SARS-CoV-2 spread in high and middle schools.